2021
DOI: 10.1111/jbi.14093
|View full text |Cite
|
Sign up to set email alerts
|

Urban tolerance of birds changes throughout the full annual cycle

Abstract: Aim: As urban areas continue to expand, it is increasingly important to quantify species-specific responses to urban environments, and how these change across the full annual cycle. Our objective was to quantify urban tolerance for North American birds across the time. We tested (a) whether intra-annual variability of urban tolerance differed between migrants and residents and (b) whether intra-annual variability of urban tolerance was phylogenetically conserved. We then assessed how the relationship between e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 96 publications
1
10
0
Order By: Relevance
“…This is noteworthy considering that others have found that predictors can have contrasting effects among seasons (La Sorte et al, 2020). We propose that temporal changes in the strength of the diversity-environment relationships can be the result of mechanisms simultaneously operating such as changes in anthropogenic food availability (Stofberg et al, 2019), the seasonal use of habitat (Marone et al, 1997), the species urban tolerance (Callaghan et al, 2021), and the anthropic related mortality (Bracey et al, 2016) among others.…”
Section: Community Diversity and Structure Responses To Green Spaces' Characteristicsmentioning
confidence: 71%
“…This is noteworthy considering that others have found that predictors can have contrasting effects among seasons (La Sorte et al, 2020). We propose that temporal changes in the strength of the diversity-environment relationships can be the result of mechanisms simultaneously operating such as changes in anthropogenic food availability (Stofberg et al, 2019), the seasonal use of habitat (Marone et al, 1997), the species urban tolerance (Callaghan et al, 2021), and the anthropic related mortality (Bracey et al, 2016) among others.…”
Section: Community Diversity and Structure Responses To Green Spaces' Characteristicsmentioning
confidence: 71%
“…Recently, an adjustment of urban affinity indices that aims to account for the potential effects of range size, sampling biases and interspecific competition has been published and provides a potential solution for biased data (Callaghan, Cornwell, et al, 2021;Callaghan, Major, et al, 2020). In any case, the scores of the indices we present should not be interpreted as absolute but as relative values of urban affinity that allow comparing different indices and species with each other but do not necessarily reflect the actual urban affinity.…”
Section: Discussionmentioning
confidence: 99%
“…Callaghan et al, 2019;Hill et al, 2002). Another interesting possibility to extend the application of the indices would be to add a temporal component, that is, to track changes in the urban affinity in the course of a year (Callaghan, Cornwell, et al, 2021) or over longer time periods. The latter could help to detect long-term effects of urbanization.…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…These spatial patterns were consistent across the summer and the monsoon seasons, but not during winter (Figure S1), where the higher dissimilarity may result from an increased number of overwintering visitors. Indeed, it has been demonstrated that urban tolerance changes through the year with different patterns for migratory and breeding/resident species (Callaghan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%